Metode Pembelajaran Bahasa Asing (Jerman) dan Sekelumit Perkembangannya - Syamsu Rijal; Syarifah Fatimah (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2019)
The method as one of the important components in the learning process needs to be better understood, because the success or failure of a learning goal depends on the type and application of the chosen method. This paper presents five types of methods that are commonly understood in learning German as a foreign language (Deutsch als Fremdsprache), namely: Grammatik-Übersetzungsmethode, direkte Methode, Audio-linguale Methode, Kommunikative Methode, interkulturelle Ansatz. These five types of methods are presented chronically to describe the process of developing the foreign (German) language learning method.